2020
DOI: 10.2174/1871526519666190916101509
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Hepatitis C Virus Among Blood Donors Attending Samarra's General Hospital

Abstract: Aim: To measure the prevalence of hepatitis C virus (HCV) among blood donors attending Samarra’a General Hospital. Patients and Methods: A questionnaire was developed in line with the study objectives. It was administered to blood donors visiting blood bank. After they were administered, informed consent and assurance with regards to confidentiality were provided. Results: A total of 50 blood donors were surveyed. The majority were males (66%) and most of them (40%) were between 21-35 years old. The ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…CNTS and KTH Blood Banks all together being located in Bujumbura city; this difference can make us think about the increasing of HCV prevalence in Bujumbura general population or Bujumbura blood donors. The prevalence found is relatively higher compared to that found by Abid and Athraa 35 at Samarra's General Hospital (2.40%), Ping et al 36 among blood donors in China (0.16%) and. Bhatti et al 27 in Pakistan (1.50%).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…CNTS and KTH Blood Banks all together being located in Bujumbura city; this difference can make us think about the increasing of HCV prevalence in Bujumbura general population or Bujumbura blood donors. The prevalence found is relatively higher compared to that found by Abid and Athraa 35 at Samarra's General Hospital (2.40%), Ping et al 36 among blood donors in China (0.16%) and. Bhatti et al 27 in Pakistan (1.50%).…”
Section: Discussionmentioning
confidence: 51%
“…Even if blood donors do not constitute a sufficient representative population for estimation of the prevalence of HBV in general population, this study shows that there is good progress in fighting against HBV. Even though, this prevalence is high compared to the countries where hepatitis B vaccination rate is high 35,36 .…”
Section: Prevalence Of Transfusion Transmitted Infectionsmentioning
confidence: 95%
“…While some studies reported high HCVAb carriage: in the southern 12% [ 34 ], in the western 6.3% [ 35 ], numerous studies on the contrary revealed a relative much lower prevalence: 2.2% anti-HCV in the Northern [ 27 ], 0.6% in the eastern [ 36 ], 0.4% in the western [ 37 ], 4.8% in the Littoral Region [ 38 ], 1.44% in the center region [ 39 ]. Equally, various burden of anti-HCV antibodies have also been reported in community settings worldwide: 0.77% in Romania [ 40 ], 1.02% in Sudan [ 41 ], 1.2% in Madagascar [ 42 ], 2.4%in Iraq [ 43 ], 3.6% in India [ 44 ], 19.80% in Cairo [ 45 ]. It is known that anti-HCV seropositivity from population-based studies is used to compare levels of HCV infection [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…While some studies reported high HCVAb carriage: in the southern 12% [35], in the western6.3% [36], numerous studies on the contrary revealed a relative much lower prevalence: 2.2% anti-HCV in the Northern [37], 0.6% in the eastern [38], 0.4% in the western [39], 4.8% in the Littoral Region [40], 1.44% in the center region [41]. Equally, various burden of anti-HCV antibodies have also been reported in community settings worldwide: 0.77% in Romania [42], 1.02% in Sudan [43], 1.2% in Madagascar [44], 2.4%in Iraq [45], 3.6% in India [46], 19.80% in Cairo [47]. It is known that anti-HCV seropositivity from population-based studies is used to compare levels of HCV infection [9].…”
Section: Liver Impairment According To Hepatitis C Antibodies Carriag...mentioning
confidence: 99%